Rethinking the fourth power dimension: organisational subject and culture change - González Cruz, Erik Geovany (2021)
This paper aims to rethink the view of the fourth power dimension, alongside the idea of the organisational subject and cultural change. This work is a theoretical review divided into six parts. The first section is an introduction regarding the discussion of power in the first three dimensions. The second part deals with the fourth power dimension. The third part reflects upon the ethical subject. The fourth section approaches the study of power in organisations, and the fifth part delves into the proposal of the organisational subject. The sixth part links the idea of the organisational subject to culture change. Finally, a series of reflexions are proposed about the possible ways to study the organisational subject.